Immunologic Response of HIV-Infected Children to Different Regimens of Antiretroviral Therapy: A Retrospective Observational Study - Teshale Ayele Mega; Firehiwot Belayneh Usamo; Getandale Zeleke Negera (AIDS Research and Treatment)
Background. Both abacavir- (ABC-) based and zidovudine- (AZT-) based regimens are widely utilized for managing HIV infection in children. Unfortunately, there is a lack of data regarding their immunological response and associated risk factors in Ethiopia. Methods. A retrospective hospital-based cohort study was conducted on HIV-infected children in Jimma Medical Center (JMC). A total of 179 records were reviewed by including data from November 2015 to April 2017. Data were collected on sociodemographic, clinical characteristics of patients and drug-related variables. Data analysis was done using STATA 13.1. Mixed-effect linear regression was performed to assess the difference in CD4+ changes between groups adjusting for baseline characteristics. The change in predicted CD4 count attributed to each regimen was also assessed by marginal analysis. P<0.05 for slope of the random-effect linear regression was used as an indicator for the presence of association. Result. Of 179 patients, 98 (54.7%) were females. The mean (±SD) duration of follow-up was 939.8 ± 478.3 and 984.92 ± 453.1 days for ABC and AZT groups, respectively. AZT group had a significant CD4+ count gain per visit compared with their ABC counterparts ((β = 20.51, 95% CI [6.37–34.65]), P=0.004) over time. The regimen AZT + 3TC + LPV/r tended to have an excellent predicted CD4+ lymphocyte count change relative to all other regimens, while ABC + 3TC + LPV/r had the least immunologic recovery (margins 338.0 cells/mm3 versus 249.13 cells/mm3 (P<0.001)). Baseline CD4+ lymphocyte count, ART group, WHO clinical stages, and viral load were independent predictors for CD4+ change overtime. Conclusion. AZT-based regimens seem to have better immunological response compared to ABC-based regimens. Immunologic response was described worse in patients with a viral load of >1000copies/ml, low baseline CD4+ count, advanced WHO clinical stages, and ABC-containing regimens. Further study is needed to clarify these aspects.